Cartal Money Restrictions: A Critical Analysis of Combating Corruption in Digital Indonesia - Syam, Muhamad Auza; Kholiq, Abdul (Law Development Journal, 2025)
The use of banknotes in high-value transactions increases vulnerability to corrupt practices that open legal loopholes for corrupt actors. Thus, the need for restrictions on banknotes can be considered as a preventive policy.  This research has two main objectives: first, to identify the factors that affect the effectiveness of restrictions on the use of banknotes in preventing corruption, and second, to analyze the legal construction related to restrictions on the use of banknotes in Indonesia.  This research uses normative legal research methods, with a statutory approach and conceptual approach. Primary data source materials are used in the form of Law Number 20 of 2001 amending Law Number 31 of 1999, concerning the Eradication of Corruption (Anti-Corruption Law), and secondary materials in the form of related books and journals are used to enrich the analysis. The results of this study show that the limitation of banknotes is an effective solution as a means of preventing corruption, considering that banknotes are the main means of corrupt practices. Currently, regulations on limiting the use of currency notes in Indonesia's legal system are still at the planning stage. For this reason, political commitment and public support are needed to realize a comprehensive regulation. This regulation is expected to encourage the transition to cashless transactions and strengthen the integrity and accountability of the national financial system. The Bill on Limiting Cartal Money Transactions (PTUK) is an important step to limit cash transactions, encourage financial digitization, and improve transparency, efficiency, and accountability. The passage of this bill can reduce the space for corruption and strengthen efforts to realize clean government.